A cross-sectional with retrospective review of chronic actinic dermatitis: A rare photodermatosis in Thailand - Alita Sombatmaithai (2019)
© 2018, Medical Association of Thailand. All rights reserved. Background: Chronic actinic dermatitis [CAD] is an idiopathic photodermatosis that has been reported worldwide and occurs mainly in elderly men with a history of chronic exposure to sunlight. Objective: To investigate the clinical characteristics, photobiological characteristics, and treatment outcomes of CAD patients in Thailand. Materials and Methods: The present study was cross-sectional retrospective chart review conducted in patients that underwent phototesting at the Photodermatology clinic of Siriraj Hospital between 1997 and 2013. Data were collected from patient medical records and follow-up telephone interviews. Complete response was defined as 100% clinical improvement, and partial response was defined as 25% to 99% clinical improvement. Results: Forty-five patients were included, of which 39 (86%) were male and six (14%) were female. The mean age was 57.5 (range 28 to 84) years. More than half of patients (51%) had decreased minimal erythema dose [MED] to both ultraviolet [UV] A and UVB, while 18 patients (40%) had decreased MED to UVB alone and four patients (9%) had decreased MED to UVA alone. Eleven patients (24%) had extensive skin involvement beyond the sun-exposed area. All patients showed some degree of clinical improvement after initiation of photoprotection and medical treatment. Analysis of clinical course was available in 35 patients, with a mean ± standard deviation follow-up duration of 24.5 (range 1 to 72) months. Six patients (17%) achieved complete response and 29 patients (83%) showed partial response to treatment. In the complete response group, the mean duration of disease was 19.67±15.15 (range 3 to 40) months and no systemic medication was required. Systemic corticosteroids and/or immunosuppressants were required in severe patients, particularly in patients who had exfoliative dermatitis or leonine facies. In patients with recalcitrant facial lesions, 0.1% tacrolimus ointment showed a promising response. Conclusion: CAD had a chronic course in the present study and only a minority of patients achieved complete response. In severe cases, lesions demonstrated a tendency to spread beyond the sun-exposed areas. UVA and UVB were the most common action spectra. In patients with recalcitrant disease, 0.1% tacrolimus ointment should be considered, especially in patients with facial lesions.